2019
DOI: 10.1016/j.ijhydene.2019.07.019
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale combustion model formulation for NO predictions in hydrogen enriched jet flames

Abstract: The present paper investigates the role of combustion models and kinetic mechanisms on the prediction of NO x emissions in a turbulent combustion system where conventional and unconventional routes are equally important for NO x formation. To this end, a lab-scale combustion system working in Moderate and Intense Low-oxygen Dilution (MILD) conditions, namely the Adelaide Jet in Hot Co-flow (JHC) burner, is targeted. The Eddy Dissipation Concept (EDC) and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

5
1

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 79 publications
(115 reference statements)
0
16
0
Order By: Relevance
“…This overestimation is likely due to the absence of the reburning route and the assumption of a global scheme for the prompt route, which was found to be the main contributor to NO formation in the corresponding study (Galletti et al, 2015). For models M5-M6, Iavarone et al (2019) found that the contribution of each pathway to the peak of NO formation at z = 200 mm is as follows (in decreasing order): NNH>thermal>prompt>N 2 O. The analysis has been extended to the other two axial locations: at z = 60 mm the rank is prompt>NNH>N 2 O>thermal, whereas at z = 120 mm the NNH contribution overcomes the prompt one and the rank is thus NNH>prompt>N 2 O>thermal.…”
Section: Cfd Modeling Of No X Emissions In Mild Conditionsmentioning
confidence: 94%
See 4 more Smart Citations
“…This overestimation is likely due to the absence of the reburning route and the assumption of a global scheme for the prompt route, which was found to be the main contributor to NO formation in the corresponding study (Galletti et al, 2015). For models M5-M6, Iavarone et al (2019) found that the contribution of each pathway to the peak of NO formation at z = 200 mm is as follows (in decreasing order): NNH>thermal>prompt>N 2 O. The analysis has been extended to the other two axial locations: at z = 60 mm the rank is prompt>NNH>N 2 O>thermal, whereas at z = 120 mm the NNH contribution overcomes the prompt one and the rank is thus NNH>prompt>N 2 O>thermal.…”
Section: Cfd Modeling Of No X Emissions In Mild Conditionsmentioning
confidence: 94%
“…In PaSR, a reacting region volume fraction κ is defined based on local estimations of chemical and mixing time scales. Better results in terms of predicted temperatures and main species concentrations in the Adelaide JHC burner have been achieved by both Reynolds Averaged Navier Stokes (RANS) and Large Eddy Simulation (LES) studies employing the PaSR model Ferrarotti et al, 2019;Iavarone et al, 2019) with respect to EDC. However, estimating the formation of NO x may require the resolution of chemical source terms with different characteristic time scales, since the reactions forming NO occur in a wider range of time scales compared to those of the main combustion process.…”
Section: Cfd Modeling Of No X Emissions In Mild Conditionsmentioning
confidence: 99%
See 3 more Smart Citations